Mapping the Intellectual Structure of Research in Employer Branding and Talent Attraction - Carmen Mandey; Deske W. Mandagi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
The growing competition for skilled talent has elevated employer branding from a supporting human resource practice to a strategic mechanism for enhancing organizational attractiveness in dynamic labor markets. Despite a rapidly expanding body of research, the employer branding and talent attraction literature remains fragmented across human resource management, marketing, and organizational studies, limiting the development of cumulative theory. This study presents a comprehensive systematic literature review (SLR) that maps the intellectual structure and evolution of research on employer branding and talent attraction using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Drawing on 78 peer-reviewed journal articles indexed in Scopus between 2007 and 2025, the review integrates bibliometric analysis and keyword co-occurrence mapping to identify dominant themes, influential contributors, and emerging research streams. The findings reveal a clear progression from early recruitment- and image-oriented perspectives toward more holistic, employee-centered approaches that emphasize talent management, employee engagement, sustainability, and digital recruitment platforms. The study also highlights persistent gaps in theoretical integration, cross-cultural analysis, and longitudinal research designs.